Analisis Dinamika Keuangan Rumah Sakit di Indonesia: Studi Komparatif RS Bunda dan RS Hermina Tahun 2022–2024 - Rosita Indriani; Aulia Ayu Hartini; Suci Zahara; Putri Batenia; Siti Sahara; Yanuar Ramadhan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze and compare the financial performance of RS Bunda and RS Hermina, two major private hospitals in Indonesia that have been publicly listed on the Indonesia Stock Exchange, during the 2022–2024 period. A descriptive comparative quantitative approach was used through financial ratio analysis, trend analysis, common size analysis, and index analysis to assess operational efficiency, capital structure, and profitability. The data analyzed were audited annual financial statements. The findings show that RS Bunda had a higher liquidity level and conservative leverage management; however, its performance declined significantly, particularly in net income and asset utilization efficiency. On the other hand, RS Hermina consistently demonstrated superior performance in terms of profitability, operational efficiency, and asset growth, supported by an efficient, leverage based expansion strategy. These findings reflect managerial differences and provide valuable insights for the development of data driven and accountable financial policies in hospital management. This study is expected to serve as a reference for strategic decision making in Indonesia’s healthcare sector.